2021
DOI: 10.1186/s12890-021-01418-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and quality of life in interstitial lung disease: a prospective cohort study

Abstract: Background Malnutrition and altered body composition are well-documented in chronic pulmonary diseases; however, investigation of nutritional status in interstitial lung disease (ILD) is limited. This study aimed to describe the nutritional status of ILD patients within three diagnostic groups and explore the relationship between nutritional status and quality of life (QoL). Methods Consecutive patients attending an ILD clinic within a tertiary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
2
21
0
2
Order By: Relevance
“…Furthermore, when considering anthropometric measurements such as waist circumference, 8.4% and 46.2% of patients in the normal weight and overweight classes showed an increase in cardiovascular risk. Our results overlap with prior observations that report a high prevalence of obesity and cardiovascular comorbidities in IPF patients [ 27 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Furthermore, when considering anthropometric measurements such as waist circumference, 8.4% and 46.2% of patients in the normal weight and overweight classes showed an increase in cardiovascular risk. Our results overlap with prior observations that report a high prevalence of obesity and cardiovascular comorbidities in IPF patients [ 27 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 73%
“…However, recent studies showed that not only overt malnutrition is a negative prognostic factor for patients with IPF, [22] but also body weight loss, sarcopenia and reduced gait speed or hand grip strength are associated with poor clinical outcomes [23][24][25][26] or reduced quality of life. [27] These conditions were observed in a considerable percentage of our normally nourished patients. Furthermore, despite our study recruited patients at the time of diagnosis, only about one third of them was classified as GAP stage 1 at enrollment, and up to 43% already reported an inactive lifestyle.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Any inhalation of recreational drugs such as tobacco, marijuana, vaping, and other products should be discontinued. Recent studies have highlighted the importance of fostering a good nutritional status to maintain respiratory function in chronic respiratory disorders, especially in patients with gastrointestinal symptoms (77)(78)(79). Annual screening for immunosuppressant-induced nonmelanoma skin cancers is also recommended.…”
Section: A Proposed Strategy For the Management Of Ssc-ildmentioning
confidence: 99%